Intussusception: Gender and Seasonal Variation and Disease Burden in Chittagong Medical College & Hospital - Bhuiyan, Md Akbar Husain; Chowdhury, Tanvir Kabir; Rahman, MA Mushfiqur; Sajid, Md Minhajuddin; Farooq, Md Abdullah Al; Sarwar, Khurshid Alam; Khastagir, Rajib; Chowdhury, Tahmina Akhter; Habib, Golam; Banu, Tahmina (Journal of Chittagong Medical College Teachers’ Association, 2014)
Intussusception is a common gastrointestinal emergency in children and appears to have a somewhat different clinical spectrum in developing countries. Its etiology is still unclear, but a link to infective agents and viruses has been highlighted. This study aimed to assess the gender and seasonal variation and the disease load of intussusception in Chittagong Medical College and Hospital (CMCH). A retrospective review of the patients of Intussusception admitted in the department of Pediatric Surgery, CMCH, Chittagong; Bangladesh from January 2009 to December 2013 was done. Help was also taken from yearly departmental audits of 2009 to 2013. Data were analyzed with regard to occurrence, seasonal variation, gender variation, diagnosis, treatment and mortality. Statistical analysis was performed by the chi-square test, and mean and percentage values were calculated. P<0.05 was considered to be statistically significant. There were 231 patients of Intussusception. Age range was 1month to 15 years with median age of 8 months. Male to Female ratio was 2.9:1. There was significant difference between the rate of occurrence of Intussusception and gender (P<0.5). There was a peak on seasonal variations of Intussusception during summer and quarterly distribution was statistically significant. Hydrostatic reduction was the most commonly performed procedure. The occurrence of Intussusception was 1.7% of all admissions. There was significant gender and seasonal variations. JCMCTA 2014 ; 25 (1): 3-7